Lifetimes and Quantum Efficiencies of Quantum Dots Deterministically Positioned in Photonic‐Crystal Waveguides. Issue 11 (21st September 2020) - Chu, Xiao‐Liu; Pregnolato, Tommaso; Schott, Rüdiger; Wieck, Andreas D.; Ludwig, Arne; Rotenberg, Nir; Lodahl, Peter
Abstract: Interfacing single emitters and photonic nanostructures enables modifying their emission properties, such as enhancing individual decay rates or controlling the emission direction. To achieve full control, the single emitter must be positioned in the nanostructures deterministically. Here, spectroscopy is used to gain spectral and spatial information about individual quantum dots (QD) in order to position each emitter in a predetermined location in a unit cell of a photonic‐crystal waveguide (PhCW). Depending on the spatial and spectral positioning within the structured nanophotonic mode, the quantum dot emission is observed to either be suppressed or enhanced. These results represent an important step towards unlocking the full potential of nanophotonic systems and will be crucial to the creation of complex multi‐emitter quantum photonic circuits. Abstract : The emission dynamics of quantum dots deterministically placed throughout photonic crystal waveguide (PhCW) unit cells are mapped. This precise spatial and spectral control unlocks the full power of nanophotonics and is an important step towards large‐scale fabrication of optimal single‐ and entangled‐photon sources, and hence the creation of complex quantum photonic circuits.